The modulation of immune cell death in connection to microRNAs and natural products - Chuang, Ya-Ting; Yen, Ching-Yu; Tang, Jen-Yang; Chang, Fang-Rong; Tsai, Yi-Hong; Wu, Kuo-Chuan; Chien, Tsu-Ming; Chang, Hsueh-Wei (Frontiers in Immunology, 2024)
Immunogenic cell death (ICD) spatiotemporally regulates damage-associated molecular patterns (DAMPs) derived from dying cancer cells to signal the immune response. Intriguingly, these DAMPs and cytokines also induce cellular responses in non-immune cells, particularly cancer cells. Several ICD-modulating natural products and miRNAs have been reported to regulate the DAMP, cytokine, and cell death responses, but they lack systemic organization and connection. This review summarizes the impacts of natural products and miRNAs on the DAMP and cytokine responses and cancer cell death responses (apoptosis, autophagy, ferroptosis, necroptosis, and pyroptosis). We establish the rationale that ICD inducers of natural products have modulating effects on miRNAs, targeting DAMPs and cytokines for immune and cancer cell death responses. In conclusion, DAMP, cytokine, and cell death responses are intricately linked in cancer cells, and they are influenced by ICD-modulating natural products and miRNAs.